Méthode de réduction de modèles pour l’analyse de structures composites à matrice élastomérique - Lejeunes, Stéphane; Boukamel, Adnane; Cochelin, Bruno (European Journal of Computational Mechanics, 2007)
In this paper we present a model reduction technique, to find the equilibrium state at finite strain of tridimensional structures which have, invariant properties in a direction. Based on finite-elements formulation, this technique consists in the projection of the unknows fields on a polynomial basis in the purpose to reduce the problem dimension. A finite-element is developped for the case of nearly-incompressible visco-hyperelastic behavior for the study of an elastomeric based beam structure.